NUMERICAL DETERMINATION OF HORIZONTAL SETTLERS PERFORMANCE - Biliaiev, M. M.; Kozachyna, V. A. (Science and Transport Progress, 2015)
Purpose.Horizontal settlers are one of the most important elements in the technological scheme of water purification. Their use is associated with the possibility to pass a sufficiently large volume of water. The important task at the stage of their designing is evaluating of their effectiveness. Calculation of the efficiency of the settler can be made by mathematical modeling. Empirical, analytical models and techniques that are currently used to solve the problem, do not allow to take into account the shape of the sump and various design features that significantly affects the loyalty to a decision on the choice of the size of the settling tank and its design features. The use of analytical models is limited only to one-dimensional solutions, does not allow accounting for nonuniform velocity field of the flow in the settler. The use of advanced turbulence models for the calculation of the hydrodynamics in the settler complex forms now requires very powerful computers. In addition, the calculation of one variant of the settler may last for dozens of hours. The aim of the paper is to build a numerical model to evaluate the effectiveness of horizontal settling tank modified design. Methodology. Numerical models are based on: 1) equation of potential flow; 2) equation of inviscid fluid vortex flow; 3) equation of viscous fluid dynamics; 4) mass transfer equation. For numerical simulation the finite difference schemes are used. The numerical calculation is carried out on a rectangular grid. For the formation of the computational domain markers are used. Findings.The models allow calculating the clarification process in the settler with different form and different configuration of baffles. Originality. A new approach to investigate the mass transfer process in horizontal settler was proposed. This approach is based on the developed CFD models. Three fluid dynamics models were used for the numerical investigation of flows and waste waters purification. Practical value.The developed models have more capacity than the existing models in Ukraine. The developed models allow calculating quickly the efficiency of water purification in settlers. The models are not computationally expensive. Calculation time of one variant of the problem takes few seconds.